Zimbabwe’s predatory state: party, military and business complex - Shumba, Jabusile Madyazvimbishi (My University, 2016)
The predatory state has received considerably less attention than the developmental state in the development literature. In this thesis I probe three understudied questions on the characteristics of the predatory state and its construction. First, what are the underlying class forces and power dynamics of a predatory state and how does it function? Second, what are the modes of accumulation that characterise the predatory state? Finally, what are the implications for development outcomes? This thesis answers these questions by examining Zimbabwe’s power elite (state, military and business) anti-developmental accumulation patterns across key economic sectors: land and agriculture, mining, transport and energy, and banking and finance. I adopt an historical approach beginning in the colonial period to understand the key choices made to explain the changing role of the state in mediating accumulation patterns and implications for development in both pre- and post-independence periods. Based on my empirical research, I suggest that the predatory state is a ruling class anti-developmental accumulation and reproduction project characterised by: (1) party and military dominance in the state; (2) state-business relations shaped by domination and capture; and (3) state-society relations shaped by violence and patronage. I differentiate the notion of predation from most political economy approaches on post-colonial Africa that emphasise the absence of central authority. I challenge the developmental state concept that views the predatory state as simply the opposite of a developmental state. Finally, I also show that contrary to suggestions that the predatory state is autonomous from society, the predatory state is also in fact deeply embedded with business albeit in a different way.
Submitted to the Development Studies, School of Social Sciences in partial fulfilment of the requirements for the Degree of Doctor of Philosophy in Development Studies University of Witwatersrand, Johannesburg, South Africa 2016
Keywords: Economic development--Zimbabwe; Poverty--Zimbabwe; Zimbabwe--Economic policy; Zimbabwe--Economic conditions; Zimbabwe--Politics and government